Penyelesaian Sengketa Transaksi Elektronik Melalui Online Dispute Resolution - Difa Ayu Puspita; Wasis Susetio (LPPM Institut Pendidikan Nusantara Global, 2026)
The development of information technology has driven the growth of electronic transactions, particularly in technology-based lending and borrowing (P2PL) and e-commerce services, which in turn has increased the potential for disputes between parties. Conventional dispute resolution mechanisms are considered less effective in the context of digital transactions that are cross-regional, fast, and technology-based, so Online Dispute Resolution (ODR) has emerged as a relevant alternative. This is especially urgent in cross-border transactions, where parties from different countries may be subject to varying legal systems, creating challenges for timely and fair dispute resolution. This study aims to examine the mechanism for resolving electronic transaction disputes through ODR and identify the challenges faced in its implementation in Indonesia. The research method used is normative legal research with a statutory approach, supported by primary, secondary, and tertiary legal materials, and strengthened by data from interviews with relevant parties, namely the BPSK of Banten Province and LAPS SJK. The results of the study indicate that although Indonesia has a legal basis that allows the implementation of ODR, the regulations are still general and do not comprehensively regulate aspects of mechanisms, procedures, legal force of decisions, and personal data protection. In addition, the implementation of ODR also faces obstacles such as limited technological infrastructure, low digital literacy of the community, and risks to data security and confidentiality. Thus, this study concludes that regulatory improvements and strengthening of support systems are necessary to ensure effective implementation of ODR, provide legal certainty, and protect the rights of parties in resolving electronic transaction disputes.